Developing Strong International Agricultural Education Programs by Understanding Cognition - Alexa J. Lamm; Amy Harder; Tracy Irani; T. Grady Roberts (Journal of International Agricultural and Extension Education, 2011)
International experiences provide culturally rich, complex situations for learners to process in both the affective and cognitive domains. By better understanding how learners process the information they receive in international settings, educators can develop quality international programs that encourage learners to more fully develop their cognitive abilities. The purpose of this study was to explore the cognitive relationships between participants’ learning styles, problem solving styles, and critical thinking dispositions in an international setting. Relationships were found between learning style preferences and critical thinking disposition, and learning style preferences and problem solving style. Given these results, instructors working in international settings should expect students to differ in terms of their cognitive processes and associated cognitive styles such as learning style. Instructors should be prepared to address these differences in style as they would in a traditional instructional setting. Further, instructors can use assessment tools to group students to work together most effectively and/or to achieve diversity in their thinking styles and approaches to solving problems.
Keywords: Teaching and learning; Instructional design and delivery; Learner characteristics; Learning theory